Influence of post-deposition annealing on structural, optical and transport properties of nanocomposite ZnO-Ag thin films. (July 2018) - Kumar, V.V. Siva; Kanjilal, D.
Abstract: Thin films of ZnO and ZnO-Ag were grown by rf sputter deposition and post-annealed in air in the 300–600 °C temperature range. Annealing caused variation in strain in ZnO films and significant improvement of ZnO in ZnO-Ag films. The partial oxidation of Ag into AgxO upon annealing of ZnO-Ag films in air resulted in increase of transmittance, absorption due to Agx O phase, weakening of surface plasmon resonance absorption due to Ag nanocrystals and an increase in fluorescence. Surface studies indicate temperature induced particle transport cause agglomeration of nanocrystals in ZnO-Ag films during post-annealing. Annealed ZnO films showed a decrease in dark current and a sixteenfold increase in photocurrent at 3 V applied bias under white light illumination due to the formation of charged acceptors / oxygen vacancy centres, which was comparable to the white light photosensitivity of as-deposited ZnO-Ag film. For low applied bias voltages, Metal-Semiconductor-Metal photoconductive detectors made with annealed ZnO-Ag films showed potential for application as efficient deep ultraviolet (DUV) photodetectors with negligible sensitivity to white light and high sensitivity to DUV light.